2004
DOI: 10.1111/j.0020-6598.2004.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Education, Work, and Crime: A Human Capital Approach*

Abstract: This article develops a model of crime in which human capital increases the opportunity cost of crime from foregone work and expected costs associated with incarceration. Older, more intelligent, and more educated adults should commit fewer street (unskilled) crimes. White collar crimes decline less (or increase) with age and education. Predictions for age–crime and education–crime relationships receive broad empirical support in self‐report data from the National Longitudinal Survey of Youth and arrest data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
285
1
21

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 455 publications
(320 citation statements)
references
References 33 publications
13
285
1
21
Order By: Relevance
“…However, according to statistics from the 1980 wave of the National Longitudinal Survey of Youth (NLSY) neither the first nor the second explanation seem to be correct. It is reported that 17% of the men with a tertiary education self-report some income from crime (Lochner 2004(Lochner , 2010. The NLSY also indicates that investments in tertiary education are associated with a substantial reduction in crime.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, according to statistics from the 1980 wave of the National Longitudinal Survey of Youth (NLSY) neither the first nor the second explanation seem to be correct. It is reported that 17% of the men with a tertiary education self-report some income from crime (Lochner 2004(Lochner , 2010. The NLSY also indicates that investments in tertiary education are associated with a substantial reduction in crime.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is well established that differences in circumstances are important in explaining differences in criminal behavior (Allingham and Sandmo, 1972;Becker, 1968;Gould, Weinberg, and Mustard, 2002;Horney, Osgood, and Marshall, 1995;Levitt, 1997;Lochner, 2004;McCarthy, 2002). The role of individual motivation, in particular prosocial motivation, is less well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Nous mentionnons tout de même que, sur des données américaines, une augmentation du niveau d'éducation secondaire réduit l'incidence de crimes violents (Lochner et Moretti, 2004). Par contre, Lochner (2004) ne trouve pas d'effet de l'éducation sur l'incidence de crimes non violents telles fraude, contrefaçon, etc.…”
Section: éDucation Et Externalités Socialesunclassified